2022
DOI: 10.1186/s13014-021-01977-1
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm for thoracic re-irradiation using biologically effective dose: a common language on how to treat in a “no-treat zone”

Abstract: Background Re-irradiation (re-RT) is a technically challenging task for which few standardized approaches exist. This is in part due to the lack of a common platform to assess dose tolerance in relation to toxicity in the re-RT setting. To better address this knowledge gap and provide new tools for studying and developing thresholds for re-RT, we developed a novel algorithm that allows for anatomically accurate three-dimensional mapping of composite biological effective dose (BED) distributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Finally, considering any re-irradiation treatment option, a thorough assessment of cumulative dose affecting both the target and surrounding normal tissue is crucial, including time interval between radiotherapy courses and individual patient-related factors in determining the risk-to-benefit ratio. Retrospective data from a single large academic center suggests composite BED 3 (α/β of 3 for normal tissue) as a useful tool to predict for toxicity following thoracic re-irradiation [ 24 ]. Established dose guidelines for re-irradiation in the thorax have been outlined by the American Radium Society (ARS) and American College of Radiology (ACR) appropriateness criteria [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, considering any re-irradiation treatment option, a thorough assessment of cumulative dose affecting both the target and surrounding normal tissue is crucial, including time interval between radiotherapy courses and individual patient-related factors in determining the risk-to-benefit ratio. Retrospective data from a single large academic center suggests composite BED 3 (α/β of 3 for normal tissue) as a useful tool to predict for toxicity following thoracic re-irradiation [ 24 ]. Established dose guidelines for re-irradiation in the thorax have been outlined by the American Radium Society (ARS) and American College of Radiology (ACR) appropriateness criteria [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the recent ESTRO Physics workshop on re-irradiation, 8 such dose accumulation capability (together with visualization) was identified as one of the highest priorities when scoring potential software tools to support safe clinical re-irradiation. Although some previous studies have reported similar approaches for the evaluation of re-irradiation treatments, 19,20 few have incorporated such functionalities into re-irradiation planning using commercially available software. [3][4][5] For the fictitious RI scenario in this study, the three re-planning strategies performed equally well (Table 2, Figure 2, Figure 3a,b), which was expected due to the large distances between PTV and relevant OARs associated with RI treatments.…”
Section: Discussionmentioning
confidence: 99%
“…During the recent ESTRO Physics workshop on re‐irradiation, 8 such dose accumulation capability (together with visualization) was identified as one of the highest priorities when scoring potential software tools to support safe clinical re‐irradiation. Although some previous studies have reported similar approaches for the evaluation of re‐irradiation treatments, 19,20 few have incorporated such functionalities into re‐irradiation planning using commercially available software 3–5 …”
Section: Discussionmentioning
confidence: 99%
“…Dose from previous treatments can be deformed to the current anatomy to evaluate potential dose overlap (Meijneke et al 2013 , Nix et al 2022 ). Thereby, being used to define safe dose tolerances in those previously treated regions (Embring et al 2021 , Andratschke et al 2022 , Brooks et al 2022 , Nix et al 2022 ). In addition, DIR-facilitated dose warping can be used to correlate places of local failure with previously planned and/or delivered dose distributions (Boman et al 2017 , McVicar et al 2018 , Skjøtskift et al 2018 , Embring et al 2021 , Nix et al 2022 ).…”
Section: Application-specific Dir Uncertaintymentioning
confidence: 99%
“…The lack of standardised toxicity scoring or cumulative DVHs over multiple treatments, partially influenced by DIR uncertainty remain reasons why the recovery of organs over time is not well quantified. The calculation of biologically effective dose can improve the understanding of normal tissue responses over time (Brooks et al 2022 , Nix et al 2022 ) and allow a better estimation of safe dose constraints during re-irradiation.…”
Section: Application-specific Dir Uncertaintymentioning
confidence: 99%